The Commission's view on the missed agricultural talks deadline - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Addressing the 40th Anniversary Conference of Agra Europe on March 31st 2003,...